2016
DOI: 10.1111/aas.12810
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the association of venous oxygenation and outcome in adult hospitalized patients

Abstract: Low venous oxygen saturation may be associated with increased mortality, morbidity and length of intensive care in patients following cardiac or abdominal surgery. However, the wide range of cut-off levels and low quality of evidence hampers the clinical application. In patients with septic shock, the present evidence does not support goal-directed therapy using venous oxygen saturation during early resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…Low venous oxygen saturation reflects impaired tissue oxygenation and is routinely used as a predictive tool and a therapeutic target to improve the care of critically ill patients [ 2 ]. Previous studies have associated impaired venous oxygen saturation with increased mortality and morbidity in both surgical patients [ 3 9 ] and patients admitted in the Intensive Care Unit (ICU) [ 10 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low venous oxygen saturation reflects impaired tissue oxygenation and is routinely used as a predictive tool and a therapeutic target to improve the care of critically ill patients [ 2 ]. Previous studies have associated impaired venous oxygen saturation with increased mortality and morbidity in both surgical patients [ 3 9 ] and patients admitted in the Intensive Care Unit (ICU) [ 10 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective cohort study, we frequently found low SvO 2 values in over half of the patients before and after RVP episodes, lasting in the majority of patients at least as long as one minute after the pacing episode. However, these pe- [7] and it is a good marker of the adequacy of the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The normal values of the SvO 2 lie between 65% and 80% [7] [21]. The associations between low SvO 2 and increased mortality and morbidity and an increased length of ICU stay after cardiac surgery, have been demonstrated in many studies [7]. In the study of Holm et al, [13] that examined 396 patients after aortic Little is known about the impact of the RVP on the SvO 2 and CO and the other different steps of the TAVR procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxygen extraction, i.e the ratio of oxygen consumption (VO2) to oxygen delivery (DO2), has been associated with increased mortality following major surgery . A systematic review on central venous saturation (ScvO2) as a surrogate marker of oxygen extraction confirmed that low values were associated with increased morbidity in patients undergoing abdominal surgery, but cut‐off levels were varying between studies . Enhancement of intraoperative oxygen delivery to pre‐specified targets is a key concept in many goal‐directed hemodynamic treatment protocols .…”
Section: Introductionmentioning
confidence: 99%